Prejudice toward Black People Characters in Kathryn Bigelow's Detroit Film - Farizky, Vicky; Zamruddin, Mardliya Pratiwi; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research deals with prejudice in the Detroit film by Kathryn Bigelow. Prejudice is the negative assessment or hostility toward an individual or group resulting in negative treatment. There are so many negative treatments from the prejudice portrayed in the Detroit film. In this research, the researcher analysed the prejudice aspects through the characterization of the characters experiencing negative treatments in the Detroit film. This research was conducted by using a qualitative research design. The data were generated from the speech, thoughts, effect, action, and looks of the characters portrayed in the film. The researcher revealed that the negative treatments in Detroit are committed by the white people police officers and experienced by the black people citizens. In conclusion, four negative treatments experienced by the characters were anti-locution, discrimination, physical attack, and extermination. Therefore, the researcher concluded that the difference between both races such as their skin tone, or the types of their hair is what generated prejudice in Detroit film. Keywords: prejudice, black people, Detroit